7+3(1-2x)=x

Simple and best practice solution for 7+3(1-2x)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(1-2x)=x equation:



7+3(1-2x)=x
We move all terms to the left:
7+3(1-2x)-(x)=0
We add all the numbers together, and all the variables
3(-2x+1)-x+7=0
We add all the numbers together, and all the variables
-1x+3(-2x+1)+7=0
We multiply parentheses
-1x-6x+3+7=0
We add all the numbers together, and all the variables
-7x+10=0
We move all terms containing x to the left, all other terms to the right
-7x=-10
x=-10/-7
x=1+3/7

See similar equations:

| 2n-7=8n+13 | | 8/x-5=3/6 | | 0.5(x+12)=8+0.75(x–28) | | 4+10=-2(4x-7) | | 80-n=-54 | | 3/5(x+2=x-4 | | -30x+15=40x+24 | | 30-4x=-130 | | 5x-9x-11=-4x+3-11 | | (x+5)5=20 | | –6y−–2y=–20 | | 5x-(2x-2)=3x-1 | | 4y=2=7=3.5 | | 4(-x=2)=-(x+3)-2x | | 112=-7(r-8) | | 15z=14z-15 | | 8x-4+3=6x+1 | | -2m-5=3-5(m+1) | | (2x+1)/5=-4 | | 9(x-9)+2=-79 | | 10=4p+8 | | –10=3(n−14)−16 | | 9y−8y=7 | | -9(c-2)=4(c-15) | | -6t=11+5t | | -6(a-3)=30-4a | | -10x-5=-5+3x | | 3a−2a=19 | | y-20=70 | | 5x+15=-3.5 | | 15n=16n-7 | | 6+2k=-2 |

Equations solver categories